Effective private schooling in post-conflict contexts : a case study of Apefe Mweya Groupe Scolaire in Rubavu District, Rwanda. - Habiyambere, Jean Philippe (My University, 2012)
The aim of this case study project was to understand the factors that determine the effectiveness at Groupe Scolaire APEFE Mweya, a parent private school in Rubavu District, Rwanda. It was motivated by a persistent decline in school quality for many public elementary schools in Rwanda while on the other hand some private schools have recorded very good results in national examinations. The review of the literature revealed the important attributes of school effectiveness research in developing countries. An enquiry was conducted using personal interviews of a small sample of fourteen participants together with observation and analysis of school documents. The findings suggest that Mweya School owes its success to adopting the moral inclusion of Hutu and Tutsi ethnic groups as a sign of overcoming historical racial discrimination, and secondly to its committed teachers (work ethos) and learners; organisation and accountability of teaching and learning; private supplementary tutoring; the recognition of work done and the motivation of the teachers and learners. The findings also found that the leadership style of the principal was not delivering according to expectations and suggestions were provided to maintain the momentum of good results.
Keywords: Private schooling; Rwanda